1994
DOI: 10.1002/j.1552-4604.1994.tb03989.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fixed‐Dose Transdermal Nicotine, Tapered‐Dose Transdermal Nicotine, and Buspirone in Smoking Cessation

Abstract: The authors compared the outcome of 208 smokers treated with fixed-dose transdermal nicotine (n = 69), tapered-dose transdermal nicotine (n = 71), or buspirone (n = 68). At baseline, there were no significant differences among the three treatment groups with regard to age, gender, educational level, duration of smoking, number of cigarettes smoked per day, concomitant disease states or drug use, or Fagerstrom score. All smokers participated in a behavior modification program. Fixed-dose transdermal nicotine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Additional file 1 and Table 1 provide study characteristics. Ninety-two studies[26-117] were RCTs involving 32,185 participants and 28[56,75,93,110,118-141] were considered as observational studies involving 145, 205 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Additional file 1 and Table 1 provide study characteristics. Ninety-two studies[26-117] were RCTs involving 32,185 participants and 28[56,75,93,110,118-141] were considered as observational studies involving 145, 205 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Serotonin (5-hydroxytryptamine; 5-HT) is associated with appetitive behavior and affective state, and previous studies support a role for 5-HT activation in aspects of the nicotine withdrawal syndrome, including CPA (Suzuki et al 1997) and anxiety-like responses (West et al 1991; Hilleman et al 1992; Hilleman et al 1994). More recently, 5-HT 2C receptor agonists and a 5-HT 2A antagonist were shown to block nicotine withdrawal-induced increases in immobility in rats subjected to the forced swim test, implicating the serotonergic system in the depressive-like effects of nicotine withdrawal (Zaniewska et al 2010).…”
Section: Recent Advances In Mechanisms Of Nicotine Withdrawal: Finmentioning
confidence: 96%
“…Clinical studies of buspirone's effects on cigarette smoking in non-cocaine users have been inconsistent. Some reports indicate that buspirone significantly increased abstinence from cigarette smoking (Hilleman et al, 1992(Hilleman et al, , 1994, but other studies found no significant effect of buspirone on smoking cessation and nicotine withdrawal symptoms (Farid and Abate, 1998;Schneider et al, 1996). Buspirone was most effective as a smoking cessation aid in high-anxiety smokers (Cinciripini et al, 1995).…”
Section: Dopamine D 3 and D 4 Antagonist Interactions With Nicotinementioning
confidence: 97%